Spontaneous Periodontitis Development in Diabetic Rats Involves an Unrestricted Expression of Inflammatory Cytokines and Tissue Destructive Factors in the Absence of Major Changes in Commensal Oral Microbiota - Claudino, Marcela; Gennaro, Gabriela; Cestari, Tania Mary; Spadella, César Tadeu [UNESP]; Garlet, Gustavo Pompermaier; Assis, Gerson Francisco (Hindawi Publishing Corporation, 2012)
Diabetes mellitus is a heterogeneous group of disorders, in which hyperglycemia is a main feature. The objective was to evaluate the involvement of RAGE, inflammatory cytokines, and metalloproteinases in spontaneous periodontitis triggered by diabetes induction. Immunohistochemical procedures for MMP-2, MMP-9, TNF-alpha, IL-1 beta, IL-6, RANKL, and RAGE were performed in rats after 1, 3, 6, 9, and 12 months of diabetes induction. Total DNA was extracted from paraffin-embedded tissues and evaluated by Real-TimePCR for 16S total bacterial load and specific periodontopathogens. Our data did not demonstrate differences in microbiological patterns between groups. In diabetic groups, an increase in RAGE-positive cells was detected at 6, 9, and 12 months, while TNF-alpha-stained cells were more prevalent at 6 and 12 months. In experimental groups, IL-beta-positive cells were increased after 12 months, IL-6 stained cells were increased at 9 and 12 months, and RANKL-positive cells at 9 months. Diabetes resulted in widespread expression of RAGE, followed by expression of proinflammatory mediators, without major alterations in oral microbial profile. The pervasive expression of cytokines suggests that spontaneous periodontitis development may be independent of microbial stimulation and may be triggered by diabetes-driven imbalance of homeostasis.